PENERAPAN METODE INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPAS KELAS IV SD NEGERI CIWANGI - Siti Nova Fitriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning Natural and Social Sciences (IPAS) in elementary schools requires active student involvement to achieve meaningful understanding of concepts. However, based on preliminary observations, the IPAS learning process in grade IV of SD Negeri Ciwangi was still dominated by teacher-centered methods, resulting in less optimal learning outcomes. This study aimed to improve students’ IPAS learning outcomes through the implementation of the inquiry method in grade IV of SD Negeri Ciwangi. The research method used was Classroom Action Research (CAR) following the Kemmis and McTaggart model, conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. The research subjects were fourth-grade students of SD Negeri Ciwangi. Data were collected through observation, learning achievement tests, and documentation. The results showed that the implementation of the inquiry method increased students’ activeness and learning outcomes. This improvement was indicated by the increase in the average learning scores and the percentage of students achieving mastery learning in each cycle. Therefore, the inquiry method is effective in improving IPAS learning outcomes of fourth-grade students at SD Negeri Ciwangi.